Trust and commitment in maintaining marriage among teachers in commuting marriage in Kota Kinabalu Sabah - Joki Perdani Sawai; Mahirah Masdin; Rezki Perdani Sawai; Balan Rathakrishnan; Syaidatun Nazirah Abu Zahrin (Human Resource Management Academic Research Society (HRMARS), 2020)
Long-distance marriages are commonly performed by dual-career couples particularly teachers. This study aimed to measure the relationship between trust and commitment with maintenance of marriage among teachers who living in commuter marriages. This study was conducted on 110 teachers around Kota Kinabalu Sabah from secondary and primary schools. The research design was a quantitative study using a set of questionnaires to get feedback from respondents. The Dyadic Trust Scale (DTS) (Larzelere & Huston, 1981), The Investment Model Scale (IMS) (Rusbult, Martz & Agnew, 1998), Relationship Maintenance Scale (RMS) (Chonody, Killian, Gabb & Dunk-West, 2017) were used to measure the variables involved. The results showed that trust and commitment are positively related to marriage maintenance. The implications of this study are for teachers to acknowledge that trust and commitment play an important role in their marriage.